Quercetin inhibits human breast cancer cell proliferation and induces apoptosis via Bcl-2 and Bax regulation - Li Zhang (2012)
Breast cancer is a disease in which cancer cells form in the tissues of the breast. The present study aimed to explore the effect of the flavonoid compound quercetin on the growth and apoptosis of human breast cancer cells. Varying concentrations (12.5, 25, 50, 100, 200 µM) of quercetin were applied to cultured MCF-7 human breast cancer cells for defined lengths of time. At 50 to 200 µM doses, quercetin significantly inhibited the proliferation of MCF-7 cells assessed by MTT colorimetry, in both dose- and time-dependent manners (P<0.05). The compound also increased apoptosis after 48 h of exposure (P<0.05). Furthermore, following quercetin treatment Bcl-2 expression decreased significantly while Bax expression increased significantly (P<0.05). In brief, quercetin inhibits cell growth and induces apoptosis in MCF-7 human breast cancer cells. The mechanisms behind these effects may stem from the downregulation of Bcl-2 protein expression and upregulation of Bax expression.